Why Accounting Students Are Intent to Engage in Digital Academic Dishonesty? - Dhea Amarsya Aulia Rachma; Pepie Diptyana (Jurnal Akuntansi dan Perpajakan, 2022)
Utilizing digital tools in learning process could arise lack of control among lectures and students. This research aims to examine whether self-efficacy, machiavellianism, and fraud diamond dimensions have influence to accounting students academic dishonesty behavior, especially in digital environment. Data was gathered by convenience sampling, and hypothesis were tested using SEM-PLS. Our hypotheses were supported, except self-efficacy and rasionalization. Pressure, opportunity, capability and ”short-cut” mindset are significant factors which encouraging digital academic dishonesty. This results implies that it is important to evaluate behavioral control systems in this digital era to maintain quality of accounting graduaters.